1, 4‐Addition of TMSCCl3 to Nitroalkenes: Efficient Reaction Conditions and Mechanistic Understanding. Issue 25 (21st May 2014) - Wu, Na; Wahl, Benoit; Woodward, Simon; Lewis, William
Abstract Improved synthetic conditions allow preparation of TMSCCl3 in good yield (70 %) and excellent purity. Compounds of the type NBu4X [X=Ph3SiF2 (TBAT), F (tetrabutylammonium fluoride, TBAF), OAc, Cl and Br] act as catalytic promoters for 1, 4‐additions to a range of cyclic and acyclic nitroalkenes, in THF at 0–25 °C, typically in moderate to excellent yields (37–95 %). TBAT is the most effective promoter and bromide the least effective. Multinuclear NMR studies (1H, 19F, 13C and 29Si) under anaerobic conditions indicate that addition of TMSCCl3 to TBAT (both 0.13 M) at −20 °C, in the absence of nitroalkene, leads immediately to mixtures of Me3SiF, Ph3SiF and NBu4CCl3. The latter is stable to at least 0 °C and does not add nitroalkene from −20 to 0 °C, even after extended periods. Nitroalkene, in the presence of TMSCCl3 (both 0.13 M at −20 °C), when treated with TBAT, leads to immediate formation of the 1, 4‐addition product, suggesting the reaction proceeds via a transient [Me3Si(alkene)CCl3] species, in which (alkene) indicates an Si⋅⋅⋅O coordinated nitroalkene. The anaerobic catalytic chain is propagated through the kinetic nitronate anion resulting from 1, 4 CCl3− addition to the nitroalkene. This is demonstrated by the fact that isolated NBu4[CH2NO2] is an efficient promoter. Use of H2CCH(CH2)2CHCHNO2 in air affords radical‐derived bicyclic products arising from aerobic oxidation.